The Scale Assessment and Validation of Microfinance Services and Household Socioeconomic Model: Using Parallel and Exploratory Factor Analyses. - W Muhammad Zainuddin B Wan Abdullah; Sarina Binti Ismail; Hafiz Muhammad Zia-ul-haq; Wan Nur Rahini Aznie Zainudin; Norhaziah Nawai (International Information and Engineering Technology Association (IIETA), 2024)
Indexed by Scopus/ERA